Conductors As A Metaphor Of “Leadership” - Zel, Ugur; Onay, Meltem (International Journal of Contemporary Economics and Administrative Sciences, 2013)
Conductors are evolving from “super-maestro” to full participation in the activities of the orchestral organization, including visioning, strategic direction, audience development and fundraising. To be effective, the musical leader of the orchestra must possess a combination of skills; the most significant of which appear to be artistic and musical skills, organizational skills and charismatic leadership.The main purpose of this research is to obtain data about the relationship between personality characteristics and leadership styles of orchestra conductors. As a next step, we also want to show that the polyphony can be conducted in an harmonious way in the organizations.In the analysis section of the research, the answers given by five conductors are classified and presented within a certain systematic method. As a conclusion, when the answers are examined it was clear that there are some common traits of personality and leadership for our small sample group of conductors. We accept this research as a predecessor of another future research which may cover a larger sample from different cultures so that we can clarify the common traits or differentiators.